Perbandingan Metode Pendekatan Kualitatif dan Pendekatan Kuantitatif dalam Penelitian Pendidikan Biologi - Nor Hossimah; Khairulnisa Khairulnisa; Mutmainnah Mutmainnah (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2025)
Research methodology is a crucial element in biology education because it determines the validity and relevance of findings, particularly when choosing a qualitative or quantitative approach. This study aims to analyze and compare the two approaches through a descriptive literature review of 26 scientific articles published between 2022 and 2025, accessed through Google Scholar, Sinta, and ResearchGate. The analysis uses content techniques to identify the characteristics, advantages, disadvantages, and application patterns of each approach. The results indicate that quantitative articles have historically been cited more often than qualitative articles, although recent trends indicate an inappropriate narrowing of citations, indicating a growing appreciation for qualitative research. In terms of quantity, the number of articles is balanced between qualitative and quantitative approaches, with 13 articles each. This finding emphasizes the importance of selecting methods appropriate to the research objectives, and the collaboration of both approaches through mixed-methods research can produce more comprehensive and applicable findings.